Faktor - Faktor yang Berhubungan dengan Waktu Tunggu terhadap Pasien Rawat Jalan - Fitri Agustina; Atikah Adyas; Achmad Djamil; PA Kodrat Pramudho; Dewi Rahayu (Universitas Malahayati Lampung, 2023)
ABSTRACT Waiting time is the time required by patients to get outpatient services from the registration or counter to enter the doctor's examination room. Long waiting times for services are one of the problems that often arise in the outpatient service installation of a hospital. The length of waiting time is calculated from the time the patient registers until he gets service by a doctor. According to the Decree of the Minister of Health of the Republic of Indonesia No.129/Menkes/SK/IV/2008, outpatient services with an indicator of waiting time for outpatient services is the time it takes from the time the patient registers until he is received/served. by a specialist is 60 minutes. This study aims to determine the factors related to the waiting time of outpatients at the Ahmad Yani Hospital in Metro City. This research is a quantitative research with a cross sectional approach. The population in this study were all outpatients with a total population of 2,171 people. The sample in this study was 165 respondents who were calculated using the Slovin formula. Sampling technique using incidental sampling technique. The results of the study obtained P-Value 0.000 with OR 21.717, it can be concluded that there is a relationship between the length of medical record provision and waiting time. P-Value 0.000 with OR 11.655, it can be concluded that there is a relationship between patient registration length and waiting time. P-Value 0.001 with OR 36,392. It can be concluded that there is a relationship between the number of patient queues and waiting time. P-Value 0.000 with OR 40.393 it can be concluded that there is a relationship between doctor delay and waiting time. The dominant factor related to waiting time can be seen from the score value, which is 40,393 Doctors carry out their duties according to the specified time. Strengthen monitoring related to doctor attendance hours so that they are present on time at outpatient polyclinics. This is done to minimize waiting time in accordance with Minister of Health Decree no. 129 in 2008. Keywords: Waiting Time, Outpatient ABSTRAK Waktu tunggu merupakan waktu yang diperlukan oleh pasien untuk mendapatkan pelayanan rawat jalan dari tempat pendaftaran atau loket sampai masuk ke ruang pemeriksaan dokter. Waktu tunggu yang lama pada pelayanan, salah satu masalah yang sering muncul di instalasi pelayanan rawat jalan sebuah rumah sakit. Penelitian ini bertujuan untuk factor yang berhungan dnegan waktu tunggu pasien rawat jalan di Rumah Sakit Ahmad Yani kota Metro. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua pasien rawat jalan dengan jumlah populasi 2.171 orang. Sampel dalam penelitian ini sebanyak 165 responden yang dihitung dengan menggunakan rumus slovin. Tehnik pengambilan sampel menggunakan menggunakan tehnik asidental sampling. Hasil penelitian didapat P-Value 0,000 dengan OR 21.717 maka dapat disimpulkan bahwa ada hubungan lama penyediaan rekam medis dengan waktu tunggu.P-Value 0,002 dengan OR 9.213 maka dapat disimpulkan bahwa ada hubungan lama pemeriksaan Pasien dengan waktu tunggu. P-Value 0,000 dengan OR 11.655 maka dapat disimpulkan bahwa ada hubungan lama pendaftaran Pasien dengan waktu tunggu. P-Value 0,001 dengan OR 36.392 maka dapat disimpulkan bahwa ada hubungan jumlah antrian Pasien dengan waktu tunggu. P-Value 0,000 dengan OR 40.393. Maka dapat disimpulkan bahwa ada hubungan keterlambatan dokter dengan waktu tunggu. factor dominan yang berhubungan dengan waktu tunggu hal ini dapat dilihat dari nilai score yaitu 40.393 Dokter menjalankan tugas sesuai dengan waktu yang ditentukan.Memperkuat monitoring terkait jam kehadiran dokter agar hadir tepat waktu di poli rawat jalan hal ini dilakukan untuk meminimalisir waktu tunggu sesuai dengan kepmenkes no 129 tahun 2008. Kata Kunci : Waktu Tunggu, Pasien, Rawat Jalan